2016
DOI: 10.1242/bio.017764
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory organ ofOctopus vulgaris: morphology, plasticity, turnover and sensory characterization

Abstract: The cephalopod olfactory organ was described for the first time in 1844 by von Kölliker, who was attracted to the pair of small pits of ciliated cells on each side of the head, below the eyes close to the mantle edge, in both octopuses and squids. Several functional studies have been conducted on decapods but very little is known about octopods. The morphology of the octopus olfactory system has been studied, but only to a limited extent on post-hatching specimens, and the only paper on adult octopus gives a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 83 publications
(98 reference statements)
2
32
0
Order By: Relevance
“…(, ). It receives fibers from the olfactory organ, through the olfactory nerve (Young, ), and may act as a switch between growth and reproduction (Di Cosmo and Polese ; Polese et al., , ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(, ). It receives fibers from the olfactory organ, through the olfactory nerve (Young, ), and may act as a switch between growth and reproduction (Di Cosmo and Polese ; Polese et al., , ).…”
Section: Discussionmentioning
confidence: 99%
“…The olfactory lobe consists of three lobules, anterior, middle, and posterior, interconnected to each other (Young,'71). Its role is recently clarified by Polese et al (2015Polese et al ( , 2016. It receives fibers from the olfactory organ, through the olfactory nerve (Young,'71), and may act as a switch between growth and reproduction Polese et al, 2015Polese et al, , 2016.…”
Section: Brain Proliferating Areasmentioning
confidence: 99%
“…After this process, a transverse histological sample of approximately 1 cm thickness of the anterior part of each organism was cut and samples were dehydrated in ethanol and placed in xylene. Afterwards, samples were embedded in paraffin (58°C) in a vacuum stove (D'Aniello et al, 2016;Polese et al, 2016;Zupo et al, 2019). Histological sections of 7 lm thick were cut with a microtome and placed on slides covered with glycerin/albumin.…”
Section: Histopathological Measurementsmentioning
confidence: 99%
“…For histological staining, the samples were placed in xylene and rehydrated in ethanol to remove the paraffin. Then, half of the sections were stained with hematoxylin to assess tissue health (Polese et al, 2016;Zupo et al, 2019). The other half of sections were stained with toluidine blue (0.2% of toluidine blue in sodium acetate buffer) to assess the abundance of hemocytes (Gabe, 1968).…”
Section: Histopathological Measurementsmentioning
confidence: 99%
“…These are best studied in gastropods (Elste et al, 1990;Habib et al, 2015;Hegedűs et al, 2004;Matsuo et al, 2016;Ohsuga et al, 2000;Soinila et al, 1990;Wyeth & Croll, 2011), although these animals may also use other transmitters like nitric oxide (Elphick, Kemenes, Staras, & O'Shea, 1995;Wyeth & Croll, 2011), FMRFamide-related peptides (Nezlin & Voronezhskaya, 1997;Suzuki, Kimura, Sekiguchi, & Mizukami, 1997), and acetylcholine (Matsuo et al, 2014) in their OSNs. Cephalopods may also use multiple transmitters in their olfactory organs including nitric oxide (Di Cosmo et al, 2000;Di Cristo, De Lisa, & Di Cosmo, 2009;Emery, 1975) and FMRFamide-related peptides (Di Cosmo & Di Cristo, 1998;Polese, Bertapelle, & Di Cosmo, 2016;Wildenburg, 1997). Scaros et al, 2018 suggested that different subsets of OSNs might use different neurotransmitters.…”
Section: Evolutionary Comparisonsmentioning
confidence: 99%